2018
DOI: 10.3389/fpls.2018.01475
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory Role of Silicon in Mediating Differential Stress Tolerance Responses in Two Contrasting Tomato Genotypes Under Osmotic Stress

Abstract: Previous studies have shown the role of silicon (Si) in mitigating the adverse effect of drought stress in different crop species. However, data are lacking on a comparison of drought tolerant and drought sensitive crop cultivars in response to Si nutrition. Therefore, the aim of this study was to elucidate the mechanism (s) by which two contrasting tomato genotypes respond to Si nutrition under osmotic stress condition. Two tomato lines contrasting in their response to drought stress were hydroponically grown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
42
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(51 citation statements)
references
References 69 publications
4
42
0
1
Order By: Relevance
“…2-5). Our observations regarding enhancement in plant development and photosynthetic parameters due to exogenous use of Si during water stress condition are in accordance with other observations in various crops (Hattori et al, 2005;Pei et al, 2010;Ming et al, 2012;Shi et al, 2016;Chen et al, 2018;Ali et al, 2018;Verma et al, 2020). The improvement of growth by application of Si corresponded to the maintenance of higher P N (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…2-5). Our observations regarding enhancement in plant development and photosynthetic parameters due to exogenous use of Si during water stress condition are in accordance with other observations in various crops (Hattori et al, 2005;Pei et al, 2010;Ming et al, 2012;Shi et al, 2016;Chen et al, 2018;Ali et al, 2018;Verma et al, 2020). The improvement of growth by application of Si corresponded to the maintenance of higher P N (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…Under limited or highly variable water, plants have developed various mechanisms of resistance to water deficit by reduction of the plant life cycle (Mitra, 2001;Cia et al, 2012). Therefore, plants have evolved in various cellular and molecular strategies to cope with water deficit (Ijaz et al, 2017;Ali et al, 2018). Abiotic stresses are estimated to reduce about 51-82% agricultural crop production.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, it was shown that the exogenous application of both GABA and proline alleviated oxidative stress in rice plants subjected to salt stress [62,63]. In addition, we have recently shown that in a drought-sensitive tomato line exposed to drought stress, the levels of both GABA and proline were increased, leading to an increase in the level of polyamines, thus contributing to stress tolerance [64]. Similarly, Si was shown to mitigate the lack of Mg in maize plant by increasing the GABA concentration [27].…”
Section: Si Regulates Source To Sink Metabolic Homeostasis and Maintamentioning
confidence: 95%
“…While sacrificing stress authenticity, an induced physiological drought represents a good proxy of drought stress effects and allows fast and easy screening procedures; of course, it must be noted that osmotic stress slightly differs from drought stress both, at the molecular and physiological level, so care should be taken when interpreting results. Osmotic stress can be obtained supplementing growth media with osmolytes causing a decrease in the water potential of the substrate, to the point that water absorption by the plant is impaired [35,43,46,48]. While, in the past a wide range of solutes has been used, it turned out that most of them are able to penetrate plant cells resulting in a range of off-target effects dependent on the solute nature [49,50].…”
Section: Drought Stress Protocolsmentioning
confidence: 99%
“…Indeed, this approach is rarely reported on tomato, with very few examples [33]. In contrast, hydroponic systems can be easily applied to both Arabidopsis and tomato [34][35][36], but with potential pitfalls, for example, PEG solutions are highly viscous and can hamper aeration of the root apparatus [43]. If side effects are not a concern, other solutes, such as sorbitol or mannitol can be used.…”
Section: Drought Stress Protocolsmentioning
confidence: 99%